2003
DOI: 10.1023/a:1025981106561
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To date, there are no clear guide lines for the treatment of LELCB. Treatments performed include both deep transurethral resection of the tumor (TUR-B) as well as partial or radical cystectomy, with or without adjuvant treatments including systemic chemotherapy and radiotherapy. The prognosis is favorable for patients presenting with the pure and predominant forms with a diploid DNA pattern and very poor for patients presenting with focal LELCB. Bladder salvage therapy by performing both TUR-B alone or combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Though uncommon, the tumor may have accompanying adenocarcinoma and squamous cell carcinoma as well 58. The overlying or adjacent urothelium may show urothelial dysplasia or carcinoma in situ 28. The present case was a pure LELC.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Though uncommon, the tumor may have accompanying adenocarcinoma and squamous cell carcinoma as well 58. The overlying or adjacent urothelium may show urothelial dysplasia or carcinoma in situ 28. The present case was a pure LELC.…”
Section: Discussionmentioning
confidence: 65%
“…Since then there have been only a few relatively small studies on LELC of urinary bladder 28. The largest study was reported by Tamas et al8 who described 17 pure 13 mixed LELC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations